Unusual anatomical variation of the sternal foramen: morphology and morphometric - Pacífico, Fernando Augusto (2023)
The sternum bone may present anatomical variations acquired during its formation process, which ranges from embryonic development to the beginning of adult life. These morphological variations do not impair function but may leave the individual susceptible to various injuries and complications. The present study aims to report a foramen found in an unusual location in the sternum and discuss, through a brief review of the literature, about the main clinical implications when this anatomical variation is unknown.